2002
DOI: 10.1139/o01-239
|View full text |Cite
|
Sign up to set email alerts
|

Cancer prevention by bovine lactoferrin and underlying mechanisms — a review of experimental and clinical studies

Abstract: In experimental studies, bovine lactoferrin (bLF) has been found to significantly inhibit colon, esophagus, lung, and bladder carcinogenesis in rats when administered orally in the post-initiation stage. Furthermore, concomitant administration with carcinogens resulted in inhibition of colon carcinogenesis, possibly by suppression of phase I enzymes, such as cytochrome P450 1A2 (CYP1A2), which is preferentially induced by carcinogenic heterocyclic amines. Enhancement of the activities of their phase II counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 29 publications
4
97
0
2
Order By: Relevance
“…[17][18][19][20] Interestingly, in experimental studies, lactoferrin has been shown to inhibit the growth of some solid tumors such as colon, esophagus, and lung tumors. 21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Interestingly, in experimental studies, lactoferrin has been shown to inhibit the growth of some solid tumors such as colon, esophagus, and lung tumors. 21,22 Interestingly, stool lactoferrin has been shown to be a sensitive marker of intestinal inflammation in patients with intestinal tract symptoms and is being used in clinical practice to identify patients with intestinal tract inflammation. 23 Our results suggest that the detection of lactoferrin protein levels in the stool might also be a practical noninvasive screening test for pancreatic inflammation or cancer invasion among patients with suspected pancreatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increased recruitment of neutrophils and compliment with an increase of lactoferrin production by epithelial cells occurs in the initial phase of infection. Although there has been extensive research efforts on the structure-function relationship of LF and its application in nutritional supplement and prevention of infections and cancers [8][9][10][11][12], studies on the regulation of LF expression by physiological stimuli has been limited [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered to be a bioactive milk protein that plays versatile roles in the immune system responses and helps to protect the body from various infections. 5,6) Many studies have already demonstrated that bovine lactoferrin (bLF) features a variety of bioactivities such as anti-bacterial, [6][7][8][9] antiviral, [10][11][12] anti-oxidative, 13) anti-tumor, [14][15][16] anti-inflammatory, [17][18][19][20] immunomodulatory, 21) analgesic 22) and antistress 23) effects. Recently, it has also been reported that oral administration of bLF to patients suffering chronic hepatitis C reduced the amount of hepatitis C virus.…”
mentioning
confidence: 99%